NaYbF4:Tb/Eu modified with organic antenna for improving performance of polymer solar cells. (10th January 2018) - Jiao, Jiqing; Gai, Shasha; Li, Yao; Shen, Wenfei; Tang, Jianguo; Wang, Yao; Huang, Linjun; Liu, Jixian; Wang, Wei; Belfiore, Laurence A.
Abstract: Inorganic-organic nanocomposites are synthesized and applied in polymer solar cells (PSCs) for improving power conversion efficiency (PEC). The hexagonal NaYbF4 :Tb/Eu nanocrystals are synthesized, and then two organic molecules, phenanthroline (Phen) and thenoyltrifluroacetone (TTA), are introduced to modify the surface of the NaYbF4 :Tb/Eu. As organic antennas, Phen and TTA can absorb UV and then transfer energy to inorganic nanocrystals. The prepared nanocomposites combine upconversion (UC) and downshift (DS) process under excitation, which can convert them into visible light. Thus, the inorganic-organic nanocomposites display photoresponse both in UV and NIR region. Two organic ligands and Tb 3+ play an indispensable role during the energy transfer process. The enhanced UC and tunable DS emission match well with absorption of active layer of PSC, which can enhance the performance of PSC. The open-circuit voltage (Voc ) and short-circuit current density (Jsc ) of the devices are about 0.77 V and 16.48 mA cm −2, respectively. And the PEC of PSC can be increased 7.85%, which is about 10.2% higher than that of the reference device without UC and DS. Graphical abstract: Enhanced performance of polymer solar cell enabled by NaYbF4:Tb/Eu modified with two organic ligands. Highlights: Monodisperse NaYbF4 :Tb/Eu@Phen, TTA nanocomposites were synthesized by two-step strategy. NaYbF4 :Tb/Eu@Phen, TTA combine UC and DS process under excitation, which displayed photoresponse both in UV and NIR region. The PEC of 7.85% was achieved in polymer solar cells.